Opportunities for tackling sexual harassment in Zimbabwe: Lessons from the Global North - Chimbunde, Pfuurai (HTS teologiese studies, 2023)
This article employs content analysis to explore lessons that can be drawn from the Global North to confront sexual harassment in higher education (HE) in Africa and Zimbabwe in particular. The slow progress in both the formulation and implementation of policies directed at mitigating sexual harassment in Zimbabwe’s tertiary institutions is a slow and worrisome journey despite a well-crafted roadmap. This article, using appreciative inquiry (AI) as a lens, presents what developed countries have put in place to deal with sexual harassment. Proposals show that policies and guidelines on sexual harassment remain paper exercise in the developing countries, and are not backed by fair reporting mechanisms and education on how to deal with sexual abuse. The study suggests that policies must not remain paper exercise and therefore have to be implemented. Universities in the Global South may partner with those from the Global North and share notes and best practices on how sexual harassment can be mitigated.Contribution: The article provides insights on how universities can improve sexual harassment policy frameworks and practices to create safe and inclusive campus environments for females so as to protect students’ well-being for sustainable development.